Stationary engineering - Steingress, Frederick M (American Technical Publishers, 2003)
A new section on condensing boilers combined with new information on soot blowers and superheater design provides coverage for licensing examination preparation, in industrial classes, or as a reference for studying boiler principles and for upgrading skills.